Nepal : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
KEY ISSUES Context: Successful elections for a new Constituent Assembly and formation of a new government have stabilized the political situation. Macroeconomic situation and outlook: Nepal's macroeconomic situation remains broadly favorable. Growth is projected to recover in 2013/14 owing to good monsoons, robust growth in services, and increased public spending. Inflation is moderating, in line with developments in India. High remittance inflows are supporting a strong external position, as well as high reserve money growth. Risks to the outlook are slightly tilted to the downside, involving slower-than-expected growth in countries hosting Nepali workers and domestic financial sector risks. Medium term prospects: While remittances are expected to continue to support the external position, the outlook for growth depends on improving the environment for private investment. This requires a decisive boost in public capital spending, and structural reforms in key areas. Financial sector: Despite progress, significant vulnerabilities remain. The recent assessment under the FSAP, Nepal's first, raised concerns about asset quality and interconnectedness, as well as financial sector infrastructure-including the legal framework-and supervision and crisis preparedness. At the same time, a largely unsupervised cooperatives sector is growing rapidly. Key policy recommendations: Monetary policy should aim at controlling the volatility and level of excess reserves in the financial system, implying a modest tightening of monetary conditions. The exchange rate peg to the Indian rupee provides a useful nominal anchor for the economy, and the real exchange rate is broadly in line with fundamentals. Capital spending needs to be boosted to provide key infrastructure, and reforms implemented to support private investment, which will help generate sustained economic growth and employment opportunities. In the financial sector, further reforms to bolster regulation and supervision, and improve financial infrastructure are needed to reduce risk and increase access to finance.